The Effect of Competency and ICT Skills on Vocational Students' Work Readiness - Hakim, Dani Rahman; Kurniawati, Desi (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
This study examined the role of internship in mediating and moderating the effect of competency and ICT skills on students' work readiness. The final sample of this study was 284 vocational accounting students in South Tangerang City. By using partial least square structural equation modeling (PLS-SEM) analysis, this study proved the direct effect of competency and internship on work readiness. On the other hand, this study also found that internships can mediate ICT skills and moderate competency on work readiness. However, this study failed in proving any direct effect of ICT skills on work readiness. This study implied that internship was critical in maximizing students' work readiness. In this context, students' ICT skills did not directly affect work readiness but must be mediated by internships. The internship is also essential to strengthen the effect of competency on student work readiness.